Provision of Notary Services in Making Preliminary Sale and Purchase Agreement Deeds for Low-Income Communities in Makassar City - Alfiana Alfiana; A. Pangerang Moenta; Muhammad Azwan (Al-Bayyinah, 2022)
This study aims to determine whether related to the authority of a Notary in providing free services in making of the sale and purchase agreement deed for low-income people and regarding of whether the imposition of sanctions had been realized or not. This research was empirical law and analyzed descriptively qualitative. From the results of the research conducted, it was determined that the provision of free legal services, especially in making of the sale and purchase agreement deed for low-income class in Makassar, had not been realized. Sanctions for notaries who provide free services had never been realized in Makassar. If in the future the public and other Notaries are reported that these obligations are not fulfilled, the Notary Supervisory Council may impose administrative sanctions on the Notary.